2016
DOI: 10.1016/j.ecoleng.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between leaf and root area indices and soil suction induced during drying–wetting cycles

Abstract: The stability and serviceability of geotechnical infrastructure may be affected by plantinduced soil suction during drying-wetting cycles, because an increase in suction would reduce hydraulic conductivity and also increase shear strength. Recent studies have been conducted to quantify suction induced during evapotranspiration (ET) and ponding in soil vegetated with non-crop species that are used for the ecological restoration of geotechnical infrastructure. However, induced suction distribution under drying-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 40 publications
1
17
1
1
Order By: Relevance
“…No correlation can be found in the present study, regardless of the presence of grasses, as well as the study carried out by Ng et al (2016b). This appeared to be contradictory with the results reported by Ng et al (2016a), who showed that for single species condition, there was a linear correlation between suction preserved and RAI. In an attempt to explain such contradiction, the suction preserved was related with ks in Fig.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…No correlation can be found in the present study, regardless of the presence of grasses, as well as the study carried out by Ng et al (2016b). This appeared to be contradictory with the results reported by Ng et al (2016a), who showed that for single species condition, there was a linear correlation between suction preserved and RAI. In an attempt to explain such contradiction, the suction preserved was related with ks in Fig.…”
Section: Discussioncontrasting
confidence: 57%
“…This suggests that upon wetting, the effects of preferential water flow created by the decayed roots due to tree-tree or tree-grass interaction affected the suction preserved much more prominently than the effects of RAI. Since there was no plant-plant interaction for the single species case tested by Ng et al (2016a), no significant preferential flow took place and this explains why RAI in their case was the predominant factor governing the suction preserved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extensive field and laboratory studies have shown that transpiration-induced suction could be maintained in the soil during and after rainfall Ng et al 2014;Rahardjo et al 2014;Leung et al 2015a;Ng et al in press). Recent research also argues that the presence of roots could affect the soil water retention properties and hence the suction responses (Bengough 2012;Carminati and Vetterlein 2013;Scholl et al 2014;Leung et al 2015b;Ng et al 2016aNg et al , 2016b. The ability of plants to preserve/maintain suction has important implications for slope stability.…”
Section: Introductionmentioning
confidence: 99%